Corporate Governance Structure and Firm Performance: Evidence from Industrial Sector in Malaysia & Singapore - Al-Manseb, Abdullah Othman Omar (2010)
This research studies the influences of corporate governance structure on firm performance in Malaysia & Singapore. The governance structure variables are board size, CEO duality, CEO tenure and audit committee. ROA & OCF are the measures of firm performance. In Malaysia, firm performance is positively correlated with board size and CEO duality but negative with CEO tenure and audit committee. In Singapore, the relationship between governance structure and firm performance is positive and significant with board structure and audit committee but negative with CEO duality and CEO tenure.